The role of custom in determining the provisions of Islamic financial transactions - Zaki, Muhammad Shahrulnaim; Zahran, Mohammad Fawwaz; Mohd Sufian, Muhammad Sufi Soulhi; Marzuki, Muhammad Nabil (2025)
The role of custom in determining the rules of Islamic financial transactions The role of custom in determining the rules of Islamic financial transactions is extremely important, because the Islamic rules contained in various books of jurisprudence are the result of the efforts of previous scholars, which were greatly influenced by the factor of custom, especially when there is no explicit text in the Holy Quran or the Sunnah of the Prophet regarding a particular issue (Ahmed Musbah, 2019). These efforts may not be suitable for application in this era due to changes in societies and their current needs, and therefore the rules of Islamic jurisprudence must be updated to meet the needs of the current era. (Ahmad Musbah, 2019). These efforts may not be appropriate for application in this era due to changes in societies and their current needs. Therefore, renewals of Sharia provisions must take into account changes in customs in order to preserve the interests of the Islamic nation (Ahmad Musbah, 2019). Custom is defined as what most people in a particular place are accustomed to, whether it be in word or deed, and it can be taken as evidence in the renewal of Sharia rulings or adopted as a rule in Islamic jurisprudence (Ahmed Musbah, 2019). In the context of financial transactions, custom is an important source of legislation because it enables Islamic jurisprudence to adapt to the increasingly complex developments and needs of the contemporary economy (Mega Bosbita, 2021). Custom can be adopted as a source for deriving legal rulings if it meets certain conditions, the most important of which are that it does not conflict with the principles of Sharia and that it achieves the public interest (Mega Bosbita, 2021). Therefore, fiqh rulings on financial transactions, such as sales, leases, and others, often take into account the prevailing customs in the local community (Ahmad Musbah, 2019).